“Iron triangle” of regulating the uterine microecology: Endometrial microbiota, immunity and endometrium - Na Zhu; Na Zhu; Xuyan Yang; Qiao Liu; Yahui Chen; Xiaolan Wang; Huanhuan Li; Hong Gao (Frontiers in Immunology, 2022)
The uterus is the core place for breeding new life. The balance and imbalance of uterine microecology can directly affect or even dominate the female reproductive health. Emerging data demonstrate that endometrial microbiota, endometrium and immunity play an irreplaceable role in regulating uterine microecology, forming a dynamic iron triangle relationship. Up to nowadays, it remains unclear how the three factors affect and interact with each other, which is also a frontier topic in the emerging field of reproductive tract microecology. From this new perspective, we aim to clarify the relationship and mechanism of the interaction of these three factors, especially their pairwise interactions. Finally, the limitations and future perspectives of the current studies are summarized. In general, these three factors have a dynamic relationship of mutual dependence, promotion and restriction under the physiological or pathological conditions of uterus, among which the regulatory mechanism of microbiota and immunity plays a role of bridge. These findings can provide new insights and measures for the regulation of uterine microecology, the prevention and treatment of endometrial diseases, and the further multi-disciplinary integration between microbiology, immunology and reproductive medicine.